Prognostic factors of patients with recurrent uterine malignancies undergoing secondary cytoreductive surgery - Chenyan Fang; Yingli Zhang; Ping Zhang; Tao Zhu (BMC, 2024)
Abstract Background Several studies have demonstrated that secondary cytoreductive surgery (SCS) for patients with recurrent uterine malignancies may improve the survival. However, the selection criteria for SCS remain to be defined. This study aimed to assess the outcome of SCS and to explore factors that may influence the prognosis. Methods Data of patients with recurrent uterine malignancies who received SCS in our hospital between January 2005 and January 2015 were retrospectively analyzed. Patients were assigned into endometrial carcinoma (EC) group and uterine sarcoma (US) group. Results 84 cases in total were involved in the study, including 47 cases with recurrent EC and 37 cases with recurrent US. The 5-year survival of cases with recurrent EC and recurrent US was 59.6% and 33.3%, respectively. Recurrent EC cases with a lower tumor grade (G1/G1-G2/G2), size of the largest tumor ≤ 6 cm, single recurrent tumor, a history of adjuvant therapy, as well as recurrent US cases with younger age, a longer disease-free interval (DFI) before SCS (≥ 12 months), no peritoneal dissemination, and a history of complete cytoreduction were associated with a longer survival. The number of recurrent tumors was found as an independent prognostic factor of SCS. Conclusion Recurrent EC cases with a lower tumor grade, smaller tumor size, single tumor, a history of adjuvant therapy, as well as recurrent US cases with younger age, a longer DFI before SCS, no peritoneal dissemination, and a history of complete cytoreduction were more likely to benefit from SCS.